2020
DOI: 10.1002/ijfe.1914
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dynamic price discovery, risk transfer and spillover among INE, WTI and Brent crude oil futures markets: Evidence from the high‐frequency data

Abstract: In order to test whether Chinese crude oil futures (INE) has already played the role of futures market and whether it has had a significant impact on international benchmark market, we construct the permanent temporary model and Information Share model based on 15 min of high‐frequency trading data from March 26, 2018 to October 30, 2018 to inspect the proportions of new information in INE and Brent markets, and use the Garbade‐Silber model to measure the risk transfer effect. Furthermore, the generalised spil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 47 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Both China's crude oil and Brent's crude oil comes mainly from the Middle East and North Africa, thus China's crude oil spot pricing mainly refers to the Brent crude oil price 4 . A previous study shows that China's crude oil market is more correlated with the Brent market compare with other major crude oil markets (Zhang and Ma, 2020), Yang et al (2020) shows that Brent markets have a unidirectional Granger causality relationship with the INE crude oil futures market. Furthermore, Antonakakis et al (2014) shows that there are spillover effects between oil prices changes and EPU index, Ma et al (2019) shows that the EPU from Europe, which including the United Kingdom., increases the volatility in Brent futures, which is the benchmark of the China's crude oil spot price.…”
Section: Out-of-sample Evaluationmentioning
confidence: 92%
“…Both China's crude oil and Brent's crude oil comes mainly from the Middle East and North Africa, thus China's crude oil spot pricing mainly refers to the Brent crude oil price 4 . A previous study shows that China's crude oil market is more correlated with the Brent market compare with other major crude oil markets (Zhang and Ma, 2020), Yang et al (2020) shows that Brent markets have a unidirectional Granger causality relationship with the INE crude oil futures market. Furthermore, Antonakakis et al (2014) shows that there are spillover effects between oil prices changes and EPU index, Ma et al (2019) shows that the EPU from Europe, which including the United Kingdom., increases the volatility in Brent futures, which is the benchmark of the China's crude oil spot price.…”
Section: Out-of-sample Evaluationmentioning
confidence: 92%
“…By using the pandemic declaration date, the intraday prices ranging from 1 August 2019 to 10 March 2020 refer to the period before the pandemic and prices from 11 March 2020 to 25 September 2020 form the sample for the period after announcing the pandemic. To overcome the problem of microstructure noise and duplicate values, the high-frequency data is aggregated into a 15 min frequency, which is the highest and best frequency and is in line with (Aslam et al 2021b;Chen et al 2022;Zhang and Ma 2021). Due to removal of the duplicate values and different number of trading days in different months, we have a different number of observations for these time periods.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The results showed that there are significant price discoveries in 11 contracts among 14 agricultural products. Zhang and Ma (2020) studied the price discovery of the crude oil market based on 15‐min high‐frequency data. These authors found that, although Chinese crude oil futures were beginning to show the function of price discovery, this was still weaker compared with Brent crude oil.…”
Section: Literature Reviewmentioning
confidence: 99%